Pengaruh Iklan BTS Selalu Ada Selalu Bisa terhadap Minat Pemakaian Aplikasi Tokopedia pada Mahasiswa Universitas Tarumanagara - Ellen Ellen; Moehammad Gafar Yoedtadi (Kiwari, 2022)
The development of communication in today's digital era gives the impact that brings many changes in human life. Especially on e-commerce Tokopedia, in increasing its appeal to increase the usage of the app, in cooperation with the idol group from South Korea named BTS. Idol group K-Pop BTS is increasingly accepted by young teenagers, of course, have an achievement and its popularity is currently rising. In the study has two variables, the variable influence of advertising and the variables of interest in the use of the application with the approach of the research is quantitative and the method of a survey of 100 respondents and the questionnaire is the instrument of the author. The respondent's data processing was tested to be valid, reliable and normal. The data analysis technique used is simple linear regression test and T test. The results of the research analysis show that the advertising influence variable has an influence on the interest variable in using the application. This statement is strengthened based on the results of the T test, that the effect of advertising (X) has a significant influence on the interest in using the application (Y) so that H0 is rejected and H1 is accepted.Perkembangan komunikasi pada era digital saat ini memberikan dampak yang membawa banyak perubahan dalam kehidupan manusia. Terutama pada e-commerce Tokopedia, dalam meningkatkan daya tariknya untuk meningkatkan pemakaian aplikasi, dengan menggandeng idol group dari Korea Selatan bernama BTS. Pada penelitian ini terdapat 2 variabel yaitu, variabel pengaruh iklan dan variabel minat pemakaian aplikasi dengan pendekatan penelitian yakni kuantitatif serta metode survei terhadap 100 responden dan kuesioner yang merupakan instrumen penulis. Pengolahan data responden teruji valid, reliabel dan normal. Teknik analisis data yang digunakan ialah uji regresi linear sederhana dan uji T. Hasil analisis penelitian menunjukkan pada variabel pengaruh iklan mempunyai pengaruh terhadap variabel minat pemakaian aplikasi. Pernyataan tersebut diperkuat berdasarkan hasil uji T, bahwa pengaruh iklan (X) memiliki pengaruh yang cukup signifikan terhadap minat pemakaian aplikasi (Y) sehingga H0 ditolak dan H1 diterima.